EFEK PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN PADA NILAI PERUSAHAAN - Liana Susanto; Sufiyati; Merry Susanti; Sofia Prima Dewi (Jurnal Akuntansi, 2021)
The research is aimed to obtain empirical evidence whether profitability, leverage, and firm size have an effect on firm value. Non-financial companies listed on the Indonesia Stock Exchange during the 2017-2019 period are used as the population. Purposive sampling was used as a sampling technique. The sample obtained is as many as 85 companies. The data is processed using EVIEWS. This research finds that profitability has no negative effect on firm value, leverage has a positive effect on firm value, and firm size has a negative effect on firm value. Keywords: Firm Value; Profitability; Leverage; Firm Size